Daily Life Activities on Smartphones and Their Effect on Battery Life for Better Personal Information Management: Smartphones and Their Effect on Battery Life for Better Personal Information Management - Khan, Inayat; Khusro, Shah; Ali, Shaukat; Din, Aziz Ud (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The ubiquity of smartphones is evident from the fact that it is present in the pocket of almost every individual. Because of the increasing computing power and the integration of other abundant resources like storage and sensors, smartphones are proving as the most common Personal Information Management (PIM) platform. Smartphones can capture a broad range of users' experiences as compared to a traditional desktop computer which is evident from the numerous smartphone apps available in app markets for the purpose. These applications capture context of a user by utilizing full resources of the smartphone, especially the sensors. However, limited battery power of smartphones has proven to be the most significant bottleneck. Currently, app-based power consumption is estimated which provide only an indication of per app power usage and is of no use to researchers. This research identifies users' common daily life activities on smartphones and critically analyses their effects on battery power. Our approach looks into the problem through the eyes of researchers working in the domain of intelligent and context-aware systems. An Android-based application called Smartphone Task-based Energy Monitoring System (STEMS) is developed for estimating power consumption rates of different daily life activities. The system collects activities and the power consumption data from the participants' smartphones operating on cellular network with GSM/GPRS and Wi-Fi capabilities. It was found that activities requiring internet connectivity are more energy hungry than others. The results so obtained may prove useful to the stakeholders, like app designers and developers, PIM managers, and the end users.